Respiratory Insufficiency - Surani, Salim; Shah, Reena; Anjum Khan, Syed (IntechOpen, 2023)
In the United States, respiratory failure accounts for 1275 cases per 100,000 people. The etiology of respiratory failure can be diverse, encompassing obstructive and restrictive lung diseases, among others. The COVID-19 pandemic led to a significant surge in respiratory failure cases among patients admitted to hospitals, particularly those requiring intensive care. This book explores the pathophysiology of respiratory failure and insufficiency associated with COVID-19 illness as well as obstructive lung disease. It also delves into respiratory insufficiency stemming from liver disease and burns and discusses the role of veno-venous extracorporeal membrane oxygenation (VV-ECMO) in managing patients with respiratory insufficiency. This book is a useful resource for medical students, residents, physicians, and nurses alike.